Metallodrug ranitidine bismuth citrate suppresses SARS-CoV-2 replication and relieves virus-associated pneumonia in Syrian hamsters - Yuan, Shuofeng; Wang, Runming; Chan, Jasper Fuk-Woo; Zhang, Anna Jinxia; Cheng, Tianfan; Chik, Kenn Ka-Heng; Ye, Zi-Wei; Wang, Suyu; Lee, Andrew Chak-Yiu; Jin, Lijian; Li, Hongyan; Jin, Dong-Yan; et al. (Nature microbiology, 2020)
SARS-CoV-2 is causing a pandemic of COVID-19, with high infectivity and significant mortality 1 . Currently, therapeutic options for COVID-19 are limited. Historically, metal compounds have found use as antimicrobial agents, but their antiviral activities have rarely been explored. Here, we test a set of metallodrugs and related compounds, and identify ranitidine bismuth citrate, a commonly used drug for the treatment of Helicobacter pylori infection, as a potent anti-SARS-CoV-2 agent, both in vitro and in vivo. Ranitidine bismuth citrate exhibited low cytotoxicity and protected SARS-CoV-2-infected cells with a high selectivity index of 975. Importantly, ranitidine bismuth citrate suppressed SARS-CoV-2 replication, leading to decreased viral loads in both upper and lower respiratory tracts, and relieved virus-associated pneumonia in a golden Syrian hamster model. In vitro studies showed that ranitidine bismuth citrate and its related compounds exhibited inhibition towards both the ATPase (IC 50 = 0.69 µM) and DNA-unwinding (IC 50 = 0.70 µM) activities of the SARS-CoV-2 helicase via an irreversible displacement of zinc( ii ) ions from the enzyme by bismuth( iii ) ions. Our findings highlight viral helicase as a druggable target and the clinical potential of bismuth( iii ) drugs or other metallodrugs for the treatment of SARS-CoV-2 infection. Drug used to treat Helicobacter pylori infection reduces SARS-CoV-2 viral loads in lungs and alleviates virus-associated pneumonia in a golden Syrian hamster model.